Discourse markers across languages : a contrastive study of second-level discourse markers in native and non-native text with implications for general and pedagogic lexicography - Siepmann, Dirk, 1966- (Routledge advances in corpus linguistics, 2005)
This book offers a corpus-based contrastive study of an almost entirely unexplored set of multi-word lexical items serving pragmatic or text-structuring functions.